2021
DOI: 10.1017/s0266467421000237
|View full text |Cite
|
Sign up to set email alerts
|

Soil-litter ant (Hymenoptera: Formicidae) community response to reforested lands of Gishwati tropical montane forest, northern-western part of Rwanda

Abstract: Recently, human activities have impacted biodiversity-rich forest in western Rwanda, creating a need to enhance restoration activities of degraded lands in the region. To evaluate the effects of reforestation activities on the community composition of soil-litter ants, research was conducted in Gishwati tropical montane forest, located in northern-western part of Rwanda. The ant fauna was studied in reforested lands dominated by regenerated native species and exotic tree species. Further, a primary forest made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…Since Rwanda is a region rich in biodiversity, more ant species might be recorded either for the first time or being new to science. In addition, only a small area has been studied so far (Nsengimana et al ., 2018; Nsengimana et al ., 2021; Nsengimana & Dekoninck, 2021; Nsengimana et al ., 2023), hence a big part of the country remains unexplored. Furthermore, the studied areas have been sampled only once using rapid sampling.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
See 4 more Smart Citations
“…Since Rwanda is a region rich in biodiversity, more ant species might be recorded either for the first time or being new to science. In addition, only a small area has been studied so far (Nsengimana et al ., 2018; Nsengimana et al ., 2021; Nsengimana & Dekoninck, 2021; Nsengimana et al ., 2023), hence a big part of the country remains unexplored. Furthermore, the studied areas have been sampled only once using rapid sampling.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…In Rwanda there is limited information on the diversity and distribution of the species in genera Camponotus, Odontomachus and Tetramorium. Only Odontomachus troglodytes Santschi, 1914(Nsengimana et al, 2018Nsengimana & Dekoninck, 2020) has been reported in Rwanda. However, a recent review of the ant species collected from Rwanda and housed at the Royal Belgium Institute of Natural Science (IG 33.894) has indicated that this is a misidentification, and all the available specimens from Rwanda are Odontomachus assiniensis (Kiko Gómez.…”
Section: Tetramorium Sericeiventre Emery 1877mentioning
confidence: 99%
See 3 more Smart Citations